'The domestic handoff': stay-at-home fathers' time-use in female breadwinner families. Issue 2 (3rd May 2016) - Latshaw, Beth A.; Hale, Stephanie I.
Abstract : This paper empirically assesses a relatively unexplored topic: the time-use of stay-at-home fathers in female breadwinner families. Using a combination of microdata from the 2003–2013 American Time Use Surveys (ATUS) and in-depth interviews conducted with 30 stay-at-home fathers living in the United States, we critically examine the time-use of male caregivers, particularly during evening and weekend hours. Findings suggest that some stay-at-home fathers and breadwinning mothers shift or swap their domestic responsibilities when their wives return home from their paid jobs, allotting husbands more time to pursue other activities. As a result, some parents continue to 'do gender' in more conventional ways during evenings and weekends, even when fathers specialize in caregiving and mothers specialize in breadwinning during the day.